Sintered material, its manufacturing method, and solid-state battery manufacturing method

JP7640271B2Active Publication Date: 2025-03-05TOYOTA JIDOSHA KK +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021014303
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-01
Publication Date
2025-03-05
Estimated Expiration
2041-02-01

AI Technical Summary

Benefits of technology

【0014】 本開示は、固体電池の充放電効率を向上させることができる焼結材料及びその製造方法並びに固体電池の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640271000004
    Figure 0007640271000004
  • Figure 0007640271000005
    Figure 0007640271000005
  • Figure 0007640271000006
    Figure 0007640271000006
Patent Text Reader

Abstract

To provide a sintering material capable of improving charge / discharge efficiency of a solid-state battery, a manufacturing method thereof and a manufacturing method of the solid-state battery.SOLUTION: The present invention relates to a manufacturing method of a sintering material in which a dense layer and a porous layer contain an oxide-based solid electrolyte having a garnet type crystal structure containing Li element, La element, A element (A is at least one selected from among Zr, Nb, Ta and Al) and O element. Porosity of the dense layer is equal to or less than 15% and a longer diameter of a pore is less than a thickness of the dense layer. Porosity of the porous layer is equal to or more than 20% and equal to or less than 59% and an average pore diameter is equal to or less than 7 μm. The sintering material includes the dense layer, the porous layer and a carbon coat layer successively.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a sintered material and a method for producing the same, and a method for producing a solid-state battery. [Background technology]

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. In the automobile industry, too, development of high-output, high-capacity batteries for electric vehicles or hybrid vehicles is underway. Among batteries, lithium secondary batteries are attracting attention because they use lithium, which has the greatest ionization tendency of all metals, as the negative electrode, which results in a large potential difference with the positive electrode and a high output voltage. Moreover, solid-state batteries have attracted attention because they use a solid electrolyte as the electrolyte between the positive electrode and the negative electrode, instead of an electrolytic solution containing an organic solvent.

[0003] Patent Document 1 discloses a Li-S battery having a three-layer structure of a sintered body of a garnet-type solid electrolyte, porous / dense / porous, in which one of the porous layers is impregnated with carbon and sulfur, and the other porous layer is impregnated with (stores) lithium.

[0004] Non-Patent Document 1 discloses a solid-state battery having a garnet-type solid electrolyte (hereinafter referred to as LLZ) in a dense layer and a porous layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2019-500737 [Non-patent literature]

[0006] [Non-Patent Document 1] Gregory T. Hitz et al., Materials Today 22(2019, Jan-Feb.), P50-57. Summary of the Invention [Problem to be solved by the invention]

[0007] In the case of a porous layer negative electrode, if the pore diameter of the porous layer is large (= the specific surface area is small, i.e. the reaction area is small), the rate at which lithium is diffused and supplied to the interface between the negative electrode and lithium during high current discharge cannot keep up with the rate at which lithium dissolves at the negative electrode, resulting in voids at the interface between the lithium and the negative electrode, and the lithium in that area is no longer able to participate in charge and discharge. This phenomenon causes the problem that lithium that has lost its electronic conduction path at the end of discharge is left behind in the pores, resulting in a decrease in charge and discharge efficiency (amount of discharged power divided by amount of charged power). Even if the pore diameter of the porous layer is reduced to address this problem, there is still the problem that the charge and discharge efficiency of the solid-state battery is insufficient. In addition, in the technology described in Patent Document 1, when the pore diameter of the porous layer is small and the specific surface area is large, the charge and discharge efficiency of the solid-state battery is insufficient. 3 However, there is a problem that the amount of carbon per pore exceeds the pore volume, making it impossible to apply the method.

[0008] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide a sintered material capable of improving the charge / discharge efficiency of a solid-state battery, a manufacturing method thereof, and a manufacturing method of a solid-state battery. [Means for solving the problem]

[0009] The method for producing a sintered material disclosed herein is a method for producing a sintered material for a solid-state battery that utilizes a lithium metal precipitation-dissolution reaction as a negative electrode reaction, comprising the steps of: A step of preparing a laminate in which a composite material for a porous layer is disposed on at least one surface of a composite material for a dense layer; sintering the laminate at a temperature of 750° C. or higher to produce a sintered body having a porous layer on at least one surface of a dense layer; immersing at least a portion of the porous layer of the sintered body in an organic solvent having a carbon source dissolved therein; drying the porous layer; the carbon source is carbonized by heat-treating the sintered body in a vacuum or an inert gas at a temperature equal to or higher than the carbonization temperature of the carbon source and equal to or higher than 720° C., and a carbon coating layer is formed on a surface of the porous layer opposite to a surface on which the dense layer is disposed; the dense layer and the porous layer each contain an oxide-based solid electrolyte having a garnet-type crystal structure containing Li, La, A (A is at least one element selected from the group consisting of Zr, Nb, Ta, and Al), and O; The dense layer has a porosity of 15% or less, and the major axis of the pores is less than the thickness of the dense layer; The porous layer has a porosity of 20% or more and 59% or less and an average pore diameter of 7 μm or less, The sintered material is characterized by having the dense layer, the porous layer, and the carbon coating layer in this order.

[0010] In the method for producing a sintered material of the present disclosure, the carbon source may be polyacrylic acid.

[0011] In the method for producing a sintered material according to the present disclosure, the carbon coating layer may have a thickness of 2 to 10 nm.

[0012] The method for producing a solid-state battery according to the present disclosure is a method for producing a solid-state battery that utilizes a lithium metal deposition-dissolution reaction as a negative electrode reaction, the solid-state battery includes the sintered material, the solid-state battery has an anode layer, a solid electrolyte layer, and a cathode layer in this order; the negative electrode layer includes the porous layer and the carbon coating layer, The solid electrolyte layer includes the dense layer.

[0013] The sintered material of the present disclosure is a sintered material for a solid-state battery that utilizes a deposition-dissolution reaction of lithium metal as a negative electrode reaction, The sintered material has a dense layer, a porous layer, and a carbon coating layer in this order, the dense layer and the porous layer each contain an oxide-based solid electrolyte having a garnet-type crystal structure containing Li, La, A (A is at least one element selected from the group consisting of Zr, Nb, Ta, and Al), and O; The dense layer has a porosity of 15% or less, and the major axis of the pores is less than the thickness of the dense layer; The porous layer has a porosity of 20% or more and 59% or less and an average pore diameter of 7 μm or less, The carbon coating layer has a density of 0.4 μg / cm on the porous layer. 2 ~2.0μg / cm 2 It is characterized by having a density of Effect of the Invention

[0014] The present disclosure can provide a sintered material capable of improving the charge / discharge efficiency of a solid-state battery, a manufacturing method thereof, and a manufacturing method of a solid-state battery. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a diagram showing an example of the relationship between the average pore size of the pores in the porous layer and the specific surface area of ​​the porous layer. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of a solid-state battery according to the present disclosure. [Diagram 3] FIG. 3 shows depth profiles of O 1s spectrum and C 1s spectrum when the surface of each of the sintered materials of Example 2 and Comparative Example 1 was scraped off by 2 nm. [Figure 4] FIG. 4 is a graph showing the charge-discharge efficiency in the second cycle of each of the half-cells of Examples 1 and 2 and Comparative Example 1. [Diagram 5] FIG. 5 shows charge / discharge curves of the half cell of Comparative Example 2. [Figure 6] FIG. 6 shows charge / discharge curves of the half cell of Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] 1. Manufacturing method of sintered materials The method for producing a sintered material disclosed herein is a method for producing a sintered material for a solid-state battery that utilizes a lithium metal precipitation-dissolution reaction as a negative electrode reaction, comprising the steps of: A step of preparing a laminate in which a composite material for a porous layer is disposed on at least one surface of a composite material for a dense layer; sintering the laminate at a temperature of 750° C. or higher to produce a sintered body having a porous layer on at least one surface of a dense layer; immersing at least a portion of the porous layer of the sintered body in an organic solvent having a carbon source dissolved therein; drying the porous layer; the carbon source is carbonized by heat-treating the sintered body in a vacuum or an inert gas at a temperature equal to or higher than the carbonization temperature of the carbon source and equal to or higher than 720° C., and a carbon coating layer is formed on a surface of the porous layer opposite to a surface on which the dense layer is disposed; the dense layer and the porous layer each contain an oxide-based solid electrolyte having a garnet-type crystal structure containing Li, La, A (A is at least one element selected from the group consisting of Zr, Nb, Ta, and Al), and O; The dense layer has a porosity of 15% or less, and the major axis of the pores is less than the thickness of the dense layer; The porous layer has a porosity of 20% or more and 59% or less and an average pore diameter of 7 μm or less, The sintered material is characterized by having the dense layer, the porous layer, and the carbon coating layer in this order.

[0017] In the present disclosure, by forming a carbon coating layer on the surface of a porous layer that contains an oxide-based solid electrolyte and meets certain conditions, it is possible to suppress the loss of electronic conduction paths and improve the charge / discharge efficiency of a solid-state battery.

[0018] The method for producing a sintered material according to the present disclosure includes (1) a preparation step, (2) a sintered body preparation step, (3) a dipping step, (4) a drying step, and (5) a carbon coating layer formation step. Each step will be described below in order.

[0019] (1) Preparation process The preparation step is a step of preparing a laminate in which a composite material for a porous layer is disposed on at least one surface of a composite material for a dense layer. In the laminate, the porous layer composite material needs to be disposed on at least one surface of the dense layer composite material, and may be disposed on both surfaces of the dense layer composite material. The dense layer composite material contains an oxide-based solid electrolyte and a sintering aid, and may contain a binder as necessary. The composite material for the porous layer contains an oxide-based solid electrolyte, a sintering aid, and a pore-forming material, and may contain a binder as necessary. The oxide-based solid electrolyte may have a garnet-type crystal structure having Li, La, A (A is at least one of Zr, Nb, Ta, and Al), and O, and may be one in which a portion of the Li element is replaced with at least one element selected from the group consisting of Al, Ga, Fe, and Si, or one in which a portion of the La element is replaced with at least one element selected from the group consisting of Ca, Sr, Ba, and Ra, or one in which the A element is Zr, and one in which a portion of the Zr element is replaced with at least one element selected from the group consisting of Nb, Ta, and Al. Oxide-based solid electrolytes are generally represented by the formula Li 7+x-y-3z E (E is at least one element selected from the group consisting of Al, Ga, Fe, and Si) z La 3-x L (L is at least one element selected from the group consisting of Ca, Sr, Ba, and Ra) x Zr 2-y M (M is at least one element selected from the group consisting of Nb, Ta, and Al) y O 12 (0≦x<3, 0≦y<2, 0≦z<0.22). The oxide-based solid electrolyte may be Li7La3Zr2O 12 , Li7La3Nb2O 12 , Li7La3Ta2O 12 may be also possible. The sintering aid may have a lower melting point than the oxide-based solid electrolyte, and examples thereof include lithium borate, aluminum oxide, gallium oxide, and lithium nitrate, as well as mixtures of at least two of these. The oxide-based solid electrolyte may be in the form of particles, and the average particle size of the oxide-based solid electrolyte particles may be 0.1 μm or more and 5.0 μm or less, or 1.5 μm or more and 2.0 μm or less. If the average particle size of the oxide-based solid electrolyte particles exceeds 5.0 μm, it becomes difficult to achieve a porosity of 15% or less in the dense layer, and it becomes difficult to achieve an average pore size of 7 μm or less in the pores of the porous layer. Examples of the pore-forming material include nylon resins, phenol resins, and acrylic resins. As the binder, any conventionally known material can be used as long as it has a melting point lower than that of the oxide-based solid electrolyte, and examples of the binder include the materials exemplified as the binder used in the positive electrode layer.

[0020] In this disclosure, the average particle size of particles is the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement, unless otherwise specified. In addition, in this disclosure, the median diameter (D50) of particles is the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order from the smallest particle size.

[0021] (2) Sintered body production process The sintered body preparation step is a step of sintering the laminate at a temperature of 750° C. or higher to prepare a sintered body having a porous layer on at least one surface of the dense layer. By firing the laminate, the dense layer composite material becomes a dense layer, and the porous layer composite material becomes a porous layer. In the laminate, when the composite material for the porous layer is disposed on both sides of the composite material for the dense layer, the sintered body has a porous layer on both sides of the dense layer. The firing temperature may be 750° C. or higher, and may be 800° C. or higher from the viewpoint of ease of handling. The dense layer and the porous layer contain an oxide-based solid electrolyte. Examples of the oxide-based solid electrolyte include those exemplified in the composite material for the dense layer and the composite material for the porous layer. The dense layer may have a porosity of 15% or less. In the present disclosure, the porosity can be calculated from the following formula. Porosity (%) = {(theoretical density - actual density) / theoretical density} x 100 The dense layer may have a long diameter of pores less than the thickness of the dense layer, for example, 8 μm or less. The dense layer may have a long diameter of pores less than the thickness of the dense layer. The long diameter of the pores in the dense layer is an indicator of whether the dense layer is penetrated, and the long diameter of the pores in the dense layer being less than the thickness of the dense layer indicates that the pores in the dense layer are not connected to the outside and are not interconnected pores. The dense layer may have a thickness of, for example, 10 μm or more and 1 mm or less. The porosity of the porous layer is sufficient if it is 20% or more and 59% or less, and may be 31% or more and 59% or less in terms of the relationship between the average pore size and the specific surface area. If the porosity of the porous layer is less than 20%, the amount of Li introduced is insufficient, and the capacity of the solid-state battery decreases. If the porosity of the porous layer is more than 59%, the strength of the porous layer decreases, and there is a possibility that the structure of the porous layer cannot be maintained. The porous layer has pores, and the pores may have communicating pores that connect to the outside. FIG. 1 is a diagram showing an example of the relationship between the average pore size of the pores in the porous layer and the specific surface area of ​​the porous layer. The average pore size (D50) of the pores in the porous layer may be equal to or larger than the crystallite size of the oxide-based solid electrolyte, may be 7 μm or less, or may be 1.5 μm or more and 2.0 μm or less. If the average pore size of the pores in the porous layer exceeds 7 μm, the surface area of ​​the porous layer becomes small, which may reduce the reactivity of Li and reduce the charge / discharge efficiency of the solid-state battery.

[0022] (3) Soaking process The immersion step is a step of immersing at least a part of the porous layer of the sintered body in an organic solvent in which a carbon source is dissolved. The immersion method is not particularly limited, and may be a dropping method from the viewpoint of easily controlling the thickness of the obtained carbon coating layer. The organic solvent may be, for example, ethanol. Examples of the carbon source include polyacrylic acid (carbonization temperature 700° C.) and phenol resin (carbonization temperature 750 to 800° C.). From the viewpoint of suppressing dissolution of the sintering aid, polyacrylic acid having a relatively low carbonization temperature may be used. In the immersion step, at least a part of the porous layer may be immersed in an organic solvent having a carbon source dissolved therein, and the porous layer may be immersed from the surface opposite to the surface on which the dense layer is disposed to a predetermined depth in the organic solvent having a carbon source dissolved therein, or the entire porous layer may be immersed in the organic solvent having a carbon source dissolved therein, or from the viewpoint of making it easier to control the thickness of the resulting carbon coating layer, the porous layer may be immersed from the surface opposite to the surface on which the dense layer is disposed to a predetermined depth in the organic solvent having a carbon source dissolved therein. The predetermined depth may be appropriately set so that a desired carbon coating layer thickness is obtained.

[0023] (4) Drying process The drying step is a step of drying the porous layer. By the drying step, the portion of the porous layer that has been immersed in the carbon source can be covered with the carbon source.

[0024] (5) Carbon Coating Layer Formation Process The carbon coating layer forming process is a process in which the sintered body is heat-treated in a vacuum or in an inert gas at a temperature equal to or higher than the carbonization temperature of the carbon source and equal to or higher than 720°C to carbonize the carbon source, and a carbon coating layer is formed on the surface of the porous layer opposite to the surface on which the dense layer is disposed. The carbon coating layer may be formed to a predetermined thickness on the surface of the porous layer opposite to the surface on which the dense layer is disposed. The carbon coating layer may have a thickness of 2 to 10 nm. The carbon coating layer (carbonized carbon source) on the porous layer has a mass of 0.4 μg / cm 2 ~2.0μg / cm 2That is, the carbon coating layer may have a density of 0.4 μg / cm on the porous layer. 2 ~2.0μg / cm 2 The density may be The carbon coat layer may be formed in a region from the surface of the porous layer opposite to the surface on which the dense layer is disposed to a predetermined depth. That is, the region from the surface of the porous layer opposite to the surface on which the dense layer is disposed to a predetermined depth may be the carbon coat layer. Even in this case, the carbon coat layer is formed on the porous layer. The predetermined depth is not particularly limited as long as the surface of the porous layer has electronic conductivity, but the lower limit may be, for example, 2 nm or more, and the upper limit may be 10 nm or less from the viewpoint that the ratio of lithium decreases and the energy density decreases as the volume ratio of carbon in the pores of the porous layer increases. In addition, when the sintered body has a porous layer on both sides of a dense layer, a carbon coating layer may be formed only on the side of one of the porous layers opposite to the side on which the dense layer is disposed. By carrying out the heat treatment in a vacuum or in an inert gas, it is possible to suppress the loss of the carbonized carbon source, as compared with the case where the heat treatment is carried out in an oxygen-containing gas. The heat treatment temperature is not particularly limited as long as it is equal to or higher than the carbonization temperature of the carbon source and is 720° C. or higher, and may be 750° C. or higher. The heat treatment time is not particularly limited as long as the carbon source can be carbonized, and may be 10 minutes or more, or may be 1 hour or less from the viewpoint of preventing the sintering aid from dissolving and causing deformation of the shape of the sintered body.

[0025] 2. Sintered materials The sintered material of the present disclosure is a sintered material for a solid-state battery that utilizes a deposition-dissolution reaction of lithium metal as a negative electrode reaction, The sintered material has a dense layer, a porous layer, and a carbon coating layer in this order, the dense layer and the porous layer each contain an oxide-based solid electrolyte having a garnet-type crystal structure containing Li, La, A (A is at least one element selected from the group consisting of Zr, Nb, Ta, and Al), and O; The dense layer has a porosity of 15% or less, and the major axis of the pores is less than the thickness of the dense layer; The porous layer has a porosity of 20% or more and 59% or less and an average pore diameter of 7 μm or less, The carbon coating layer has a density of 0.4 μg / cm on the porous layer. 2 ~2.0μg / cm 2 It is characterized by having a density of

[0026] The sintered material of the present disclosure is obtained by the above-mentioned "1. Manufacturing method of sintered material". The sintered material has a dense layer, a porous layer, and a carbon coating layer in this order. The sintered material may have a porous layer, a dense layer, a porous layer, and a carbon coating layer in this order. The dense layer, the porous layer, and the carbon coating layer may be the same as those described in "1. Manufacturing method of sintered material" above.

[0027] 3. Manufacturing method of solid-state batteries The method for producing a solid-state battery according to the present disclosure is a method for producing a solid-state battery that utilizes a lithium metal deposition-dissolution reaction as a negative electrode reaction, the solid-state battery includes the sintered material, the solid-state battery has an anode layer, a solid electrolyte layer, and a cathode layer in this order; the negative electrode layer includes the porous layer and the carbon coating layer, The solid electrolyte layer includes the dense layer.

[0028] The solid-state battery of the present disclosure can be manufactured, for example, by using a dense layer, a porous layer, and a carbon coating layer in this order in a sintered material obtained by the above "1. Manufacturing method of sintered material", using the dense layer as a solid electrolyte layer, using the porous layer and the carbon coating layer as a negative electrode layer, and using a conventionally known positive electrode material for the positive electrode layer, arranging the positive electrode layer, solid electrolyte layer, and negative electrode layer in this order, and, as necessary, arranging a positive electrode current collector on the positive electrode layer side and an anode current collector on the negative electrode layer side. When the sintered material obtained by the above "1. Manufacturing method of sintered material" has a porous layer, a dense layer, a porous layer, and a carbon coating layer in this order, the porous layer and the carbon coating layer on the side where the carbon coating layer is arranged may be used as a negative electrode layer, and the porous layer on the side where the carbon coating layer is not arranged may be used as a positive electrode layer.

[0029] FIG. 2 is a schematic cross-sectional view showing an example of a solid-state battery according to the present disclosure. 2, the solid-state battery 100 includes, in this order, a negative electrode current collector 11, a carbon coating layer 12, a porous layer 13, a dense layer 14, a positive electrode layer 15, and a positive electrode current collector 16. The solid-state battery 100 includes the carbon coating layer 12 and the porous layer 13 as a negative electrode layer 17, and the dense layer 14 as a solid electrolyte layer 18. The sintered material 19 includes, in this order, the carbon coating layer 12, the porous layer 13, and the dense layer 14.

[0030] [Negative electrode] The negative electrode includes a negative electrode layer and, optionally, a negative electrode current collector.

[0031] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, and examples thereof include SUS, copper, and nickel. Examples of the form of the negative electrode current collector include foil and plate. The planar shape of the negative electrode current collector is not particularly limited, and examples thereof include a circle, an ellipse, a rectangle, and any polygonal shape. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.

[0032] [Negative electrode layer] The negative electrode layer includes a carbon coating layer and a porous layer. The carbon coating layer and the porous layer may be the same as those described in "1. Manufacturing method of sintered material" above. The porous layer of the negative electrode layer may contain a negative electrode active material after the production or charging of the solid-state battery. Examples of the negative electrode active material include metallic lithium (Li) and lithium alloys, etc. Examples of the lithium alloy include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At.

[0033] [Solid electrolyte layer] The solid electrolyte layer includes a dense layer, or may be composed of only a dense layer. The dense layer may be the same as that described in "1. Manufacturing method of sintered material" above. The thickness of the solid electrolyte layer is not particularly limited, and may be, for example, 10 μm or more and 1 mm or less.

[0034] In the solid-state battery of the present disclosure, as long as the positive electrode layer and the negative electrode layer are separated by the solid electrolyte layer, a separator impregnated with a liquid electrolyte may be disposed between the positive electrode layer and the solid electrolyte layer, or the positive electrode side may be filled with an electrolytic solution containing an electrolyte. The electrolyte may be a non-aqueous electrolyte solution, a gel electrolyte, etc. These may be used alone or in combination of two or more.

[0035] The non-aqueous electrolyte solution used generally contains a lithium salt and a non-aqueous solvent. Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6; and organic lithium salts such as LiCF3SO3, LiN(SO2CF3)2(Li-TFSI), LiN(SO2C2F5)2, and LiC(SO2CF3)3. Examples of the non-aqueous solvent include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, sulfolane, acetonitrile (AcN), dimethoxymethane, 1,2-dimethoxyethane (DME), 1,3-dimethoxypropane, diethyl ether, tetraethylene glycol dimethyl ether (TEGDME), tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide (DMSO), and mixtures thereof. From the viewpoint of ensuring a high dielectric constant and a low viscosity, a mixture of a cyclic carbonate compound having a high dielectric constant and a high viscosity, such as EC, PC, or BC, and a chain carbonate compound having a low dielectric constant and a low viscosity, such as DMC, DEC, or EMC, is preferred, and a mixture of EC and DEC is more preferred. The concentration of the lithium salt in the non-aqueous electrolyte may be, for example, 0.3 to 5M.

[0036] A gel electrolyte is generally a gel formed by adding a polymer to a non-aqueous electrolyte solution. Specifically, the gel electrolyte can be obtained by adding a polymer such as polyethylene oxide, polypropylene oxide, polyacrylonitrile, polyvinylidene fluoride (PVdF), polyurethane, polyacrylate, or cellulose to the nonaqueous electrolyte solution described above and gelling the solution.

[0037] The material of the separator is not particularly limited as long as it is a porous film, and examples thereof include resins such as polyethylene (PE), polypropylene (PP), polyester, cellulose, and polyamide. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer structure separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be a nonwoven fabric such as a resin nonwoven fabric or a glass fiber nonwoven fabric.

[0038] [Positive electrode] The positive electrode includes a positive electrode layer and, optionally, a positive electrode current collector.

[0039] [Positive electrode layer] The positive electrode layer includes a positive electrode active material, and may include, as optional components, a solid electrolyte, a conductive material, a binder, etc. The positive electrode layer may include a porous layer on the side where the carbon coating layer is not disposed.

[0040] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for a solid-state battery can be used. When the solid-state battery is a solid-state lithium secondary battery, the positive electrode active material can be, for example, metallic lithium (Li), a lithium alloy, LiCoO2, LiNi x Co 1-x O2(0 <x<1)、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples of the Li-Mn spinel substituted with a different element include LiO2, LiMnO2, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, and Li4SiO4, transition metal oxides, TiS2, Si, SiO2, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with a different element is, for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5 O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5O4, LiMn 1.5 Fe 0.5 O4 and LiMn 1.5 Zinc 0.5 O4, etc. Lithium titanate is, for example, Li4Ti5O 12 Examples of the lithium metal phosphate include LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. Examples of the transition metal oxide include V2O5 and MoO3. Examples of the lithium storage intermetallic compound include Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb. Examples of the lithium alloy include the lithium alloys exemplified as the lithium alloys used in the negative electrode active material. The shape of the positive electrode active material is not particularly limited, but may be in the form of particles. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. Meanwhile, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coverage of the coating layer on the surface of the positive electrode active material is, for example, 70% or more, and may be 90% or more.

[0041] As the solid electrolyte, the above-mentioned oxide-based solid electrolyte can be exemplified. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.

[0042] The conductive material may be a known material, such as a carbon material and metal particles. The carbon material may be at least one selected from the group consisting of acetylene black, furnace black, VGCF, carbon nanotubes, and carbon nanofibers. Among them, from the viewpoint of electronic conductivity, at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers may be used. The metal particles may be particles of Ni, Cu, Fe, SUS, etc. The content of the conductive material in the positive electrode layer is not particularly limited.

[0043] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode layer is not particularly limited.

[0044] The thickness of the positive electrode layer is not particularly limited.

[0045] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a positive electrode layer slurry, and the positive electrode layer slurry is applied onto one side of a support such as a positive electrode current collector and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, heptane, and N-methyl-2-pyrrolidone. The method for applying the positive electrode layer slurry onto one surface of a support such as a positive electrode current collector is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.

[0046] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a press pressure of about 1 MPa to 600 MPa is usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.

[0047] [Positive electrode current collector] A solid-state battery usually has a positive electrode current collector that collects current from the positive electrode layer. The positive electrode current collector may be a known metal that can be used as a current collector for solid-state batteries. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and it may be in various shapes such as a foil shape, a mesh shape, or the like.

[0048] The solid-state battery may include an exterior body that houses the positive electrode layer, the negative electrode layer, the solid electrolyte layer, and the like, as necessary. The material of the exterior body is not particularly limited as long as it is stable to the electrolyte, and examples of the material include polypropylene, polyethylene, and resins such as acrylic resin.

[0049] The solid-state battery may be a primary battery or a secondary battery, but may be a secondary battery. The secondary battery can be repeatedly charged and discharged. The secondary battery is useful, for example, as an in-vehicle battery. The solid-state battery may be a solid-state lithium secondary battery. Examples of the shape of the solid-state battery include a coin type, a laminate type, a cylindrical type, and a square type.

[0050] In the present disclosure, the lithium secondary battery refers to a battery that uses at least one of metallic lithium and a lithium alloy as the negative electrode active material and utilizes the deposition-dissolution reaction of metallic lithium as the negative electrode reaction. In addition, in the present disclosure, the negative electrode refers to one that includes a negative electrode layer. EXAMPLES

[0051] Example 1 (A) Preparation process Li 7+x-y La 3-x Ca x Zr 2-y Nb y O 12 A porous layer composite (mixed powder) consisting of oxide solid electrolyte particles (average particle size 1.5 μm) having a garnet-type crystal structure represented by (x=0.05, y=0.25), a pore former (acrylic resin beads), and a sintering aid (a mixture of lithium borate and gallium oxide), and a dense layer composite (powder) consisting of the oxide solid electrolyte and a sintering aid (a mixture of lithium borate and gallium oxide) were prepared. These were then stacked in the order of the porous layer composite, dense layer composite, and porous layer composite, and pressed to obtain a laminate. (B) Sintered body preparation process The laminate was fired at 800°C in an oxygen atmosphere to obtain a sintered body having, in this order, a porous layer (thickness 50 μm, porosity 59%, average pore diameter 1.7 μm), a dense layer (thickness 900 μm, porosity 15%, long diameter of pores 8 μm), and a porous layer (thickness 50 μm, porosity 59%, average pore diameter 1.7 μm). (C) Soaking process A precursor solution was prepared by dissolving polyacrylic acid (residual carbon content 10%) as a carbon source in ethanol. The amount of the precursor solution shown in Table 1 below was dropped onto one of the porous layers of the sintered body so that the thickness of the resulting carbon coating layer would be 2 nm. (D) Drying process The surface of the porous layer was dried and coated with polyacrylic acid. The porous layer coated with polyacrylic acid is hereafter referred to as the "negative electrode." The porous layer not coated with polyacrylic acid is hereafter referred to as the "positive electrode." (E) Carbon Coating Layer Forming Process The sintered body is heat-treated at 750°C in a high vacuum of 0.1 Pa or less to carbonize the polyacrylic acid on the surface of the porous layer, and a carbon coating layer (specific gravity 2 g / cm) is formed on the surface of the porous layer. 3 ) was formed to obtain a sintered material. The weight of the carbon coating layer (carbon) on the porous layer was 0.4 μg / cm 2 That is, the carbon coating layer has a density of 0.4 μg / cm on the porous layer. 2 has a density of [Preparation of half-cell for evaluation] A negative electrode current collector was made by applying Cu paste to the carbon coating layer and sintering it at 600° C. Furthermore, a lithium foil was attached to the surface of the porous layer on the positive electrode side to prepare a half cell for evaluating the negative electrode.

[0052] Comparative Example 1 A half cell for evaluating a negative electrode was prepared in the same manner as in Example 1, except that the above (C) immersion step, (D) drying step, and (E) carbon coating layer forming step were not performed, and a sintered body obtained by (B) sintered body preparation step, i.e., a sintered material having no carbon coating layer on the surface of the porous layer, was used.

[0053] Example 2 A sintered material was obtained in the same manner as in Example 1, except that in the above (C) immersion step, the amount of precursor solution shown in Table 1 below was dropped so that the thickness of the resulting carbon coating layer was 10 nm, and a half cell for evaluating the negative electrode was produced using the sintered material. The weight of the carbon coating layer (carbon) on the porous layer was 2.0 μg / cm 2 That is, the carbon coating layer is 2.0 μg / cm on the porous layer. 2 has a density of

[0054] Comparative Example 2 A sintered material was obtained in the same manner as in Example 1, except that in the above (E) carbon coating layer formation step, the heat treatment temperature was changed from 750°C to 700°C, and a half cell for evaluating the negative electrode was produced using the sintered material.

[0055] Comparative Example 3 A sintered material was obtained in the same manner as in Example 1, except that in the above (C) immersion step, a phenolic resin was used instead of polyacrylic acid as the carbon source, and in the (E) carbon coating layer formation step, the heat treatment temperature was changed from 750°C to 700°C. A half cell for evaluating the negative electrode was produced using the sintered material.

[0056] [Table 1]

[0057] [Carbon coat layer thickness evaluation] For the sintered materials of Example 2 and Comparative Example 1, the thickness of the carbon coating layer was evaluated by depth profile measurement using X-ray photoelectron spectroscopy (XPS). FIG. 3 shows depth profiles of O 1s spectrum and C 1s spectrum when the surface of each of the sintered materials of Example 2 and Comparative Example 1 was scraped off by 2 nm. 3, a peak indicating the presence of C-C bonds (carbon) was detected over a depth of 10 nm from the surface in the sintered material in which a carbon coating layer was formed on the porous layer surface of Example 2. On the other hand, no peak indicating the presence of C-C bonds (carbon) was detected in the depth direction in the sintered material in which a carbon coating layer was not formed on the porous layer surface of Comparative Example 1.

[0058] [Charge / discharge efficiency evaluation] Each half-cell of Examples 1 and 2 and Comparative Examples 1 to 3 was charged and discharged under the conditions shown in Table 2, and the charge-discharge efficiency (discharge capacity / charge capacity) of each half-cell was evaluated. The charge-discharge efficiency of each half-cell of Examples 1 and 2 and Comparative Example 1 in the first and second cycles is shown in Table 3. In each half-cell of Comparative Example 2 and Comparative Example 3, a side reaction other than the charging and discharging of the battery occurred, and the discharge did not appear to be completed, so the charge-discharge efficiency was "impossible to measure." FIG. 4 is a graph showing the charge-discharge efficiency in the second cycle of each of the half-cells of Examples 1 and 2 and Comparative Example 1.

[0059] [Table 2]

[0060] [Table 3]

[0061] As shown in Table 3, the charge-discharge efficiency in the second cycle of each of the half-cells of Examples 1 and 2 is higher than the charge-discharge efficiency in the second cycle of the half-cell of Comparative Example 1. FIG. 5 shows charge / discharge curves of the half cell of Comparative Example 2. FIG. 6 shows charge / discharge curves of the half cell of Comparative Example 3. 5 and 6, in each of the half-cells of Comparative Examples 2 and 3, the discharged amount of electricity continued to be discharged even after the amount of electricity discharged reached the amount of electricity charged, which suggests that a side reaction other than charging and discharging occurred. This is presumably because the heat treatment temperature of the carbon source was low, and therefore the carbon coating layer was not sufficiently formed. [Explanation of symbols]

[0062] 11 Negative electrode current collector 12 Carbon coating layer 13 Porous layer 14 Layer compacta 15 Positive electrode layer 16 Positive electrode current collector 17 Negative electrode layer 18 Solid electrolyte layer 19 Sintered materials 100 solid state battery

Claims

1. A method for producing a sintered material for a solid-state battery using a lithium metal deposition-dissolution reaction as a negative electrode reaction, comprising: A step of preparing a laminate in which a composite material for a porous layer is disposed on at least one surface of a composite material for a dense layer; sintering the laminate at a temperature of 750° C. or higher to produce a sintered body having a porous layer on at least one surface of a dense layer; immersing at least a portion of the porous layer of the sintered body in an organic solvent having a carbon source dissolved therein; drying the porous layer; the carbon source is carbonized by heat-treating the sintered body in a vacuum or in an inert gas at a temperature equal to or higher than the carbonization temperature of the carbon source and equal to or higher than 720° C.; and forming a carbon coating layer on a surface of the porous layer opposite to a surface on which the dense layer is disposed, the dense layer and the porous layer are made of an oxide-based solid electrolyte having a garnet-type crystal structure containing Li, La, A (A is at least one element selected from the group consisting of Zr, Nb, Ta, and Al), and O; The dense layer has a porosity of 15% or less, and the major axis of the pores is less than the thickness of the dense layer; The porous layer has a porosity of 20% or more and 59% or less and an average pore diameter of 7 μm or less, A method for producing a sintered material, characterized in that the sintered material has the dense layer, the porous layer, and the carbon coating layer in this order.

2. The method for producing a sintered material according to claim 1 , wherein the carbon source is polyacrylic acid.

3. The method for producing a sintered material according to claim 1 or 2, wherein the carbon coating layer has a thickness of 2 to 10 nm.

4. A method for producing a solid-state battery using a lithium metal deposition-dissolution reaction as a negative electrode reaction, comprising: The solid-state battery comprises the sintered material according to any one of claims 1 to 3, the solid-state battery has an anode layer, a solid electrolyte layer, and a cathode layer in this order; the negative electrode layer includes the porous layer and the carbon coating layer, The solid electrolyte layer includes the dense layer.

5. A sintered material for a solid-state battery that utilizes a lithium metal deposition-dissolution reaction as a negative electrode reaction, The sintered material has a dense layer, a porous layer, and a carbon coating layer in this order, the dense layer and the porous layer are made of an oxide-based solid electrolyte having a garnet-type crystal structure containing Li, La, A (A is at least one element selected from the group consisting of Zr, Nb, Ta, and Al), and O; The dense layer has a porosity of 15% or less, and the major axis of the pores is less than the thickness of the dense layer; The porous layer has a porosity of 20% or more and 59% or less and an average pore diameter of 7 μm or less, The carbon coating layer has a density of 0.4 μg / cm on the porous layer. 2 ~2.0 μg / cm 2 1. A sintered material having a density of

Citation Information

Patent Citations

  • Solid-state Li-S battery and method for fabricating same

    JP2019500737A

  • Composite structure, lithium battery, and method for manufacturing composite structure

    JP2020077571A

  • Method for producing carbon-coated solid electrolyte particle

    JP2020135947A

  • All-solid-state lithium ion secondary battery and method for manufacturing same, and negative electrode laminate sheet

    WO2020196040A1